Deep brain stimulation improves survival in severe Parkinson's disease. Issue 1 (10th July 2013) - Ngoga, Desire; Mitchell, Rosalind; Kausar, Jamilla; Hodson, James; Harries, Anwen; Pall, Hardev
Abstract : Objectives: Levodopa and other dopaminergic treatments have not had the expected effect on survival in Parkinson's disease (PD). Bilateral subthalamic nucleus deep brain stimulation (STN-DBS) has been shown to improve motor function, motor fluctuations, health-related quality of life, and to reduce medication usage and drug-induced dyskinesia in patients with severe PD refractory to medical therapy. Little however, has been described on the impact of STN-DBS on the survival of these patients. We aim in this study to examine the impact of STN-DBS on the survival of patients with severe PD. Methods: Patients who were eligible for STN-DBS were given the choice of undergoing surgery or continuing on medical treatment. Those who exercised patient choice and preferred to continue with medical treatment formed a control population. All eligible patients seen in a 10-year period are included in this study. Our primary outcome measure is a difference in mortality between the two groups with a secondary measure of admission rates to residential (nursing home) care. Results: 106 patients underwent STN-DBS, and 41 patients exercised patient choice and declined the procedure. The two groups were matched for age, gender, ethnicity, duration of disease, rates of pre-existing depression and Levodopa equivalent doses of anti-Parkinson's medications taken. Patients undergoing STN-DBS had significantly longer survival and were significantly less likely to be admitted to a residential care home than those managed purely medically. The statistical significance of these findings persisted after adjusting for potential confounding factors (survival: p=0.002, HR 0.29 (0.13 to 0.64) (residential care home admission: OR: 0.1 (95% CI 0.0 to 0.3; p<0.001). Interpretation: We show for the first time that there is a survival advantage of DBS surgery in advanced PD. The effect of potential bias factors is examined. The survival advantage may arise for several postulated reasons, ranging from improvement in axial functions, such as swallowing, to some as yet unrecognised benefit of reduction in dopaminergic medication. These findings are of great interest to both patients with PD and the health professionals considering the treatment options for patients with severe PD.